2020
DOI: 10.3389/fimmu.2020.01325
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Lung Inducible Bronchus Associated Lymphoid Tissue Is Regulated by Mycobacterium tuberculosis Expressed Determinants

Abstract: Mycobacterium tuberculosis (Mtb) is the causative agent of the infectious disease tuberculosis (TB), which is a leading cause of death worldwide. Approximately one fourth of the world's population is infected with Mtb. A major unresolved question is delineating the inducers of protective long-lasting immune response without inducing overt, lung inflammation. Previous studies have shown that the presence of inducible Bronchus-Associated Lymphoid Tissue (iBALT) correlate with protection from Mtb infection. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…1j ) 32,33 . Consistent with previously published studies in mice and NHPs 34,35 , we found iBALT-like structures containing B220 + and CD3e + T-lymphocytes mainly in the wt-mouse lung with fewer Ly6G + neutrophils and F4/80 + macrophages. In contrast, Ly6G + myeloid clusters were seen throughout the lung of Il1r1 −/− mice.…”
Section: Resultssupporting
confidence: 93%
“…1j ) 32,33 . Consistent with previously published studies in mice and NHPs 34,35 , we found iBALT-like structures containing B220 + and CD3e + T-lymphocytes mainly in the wt-mouse lung with fewer Ly6G + neutrophils and F4/80 + macrophages. In contrast, Ly6G + myeloid clusters were seen throughout the lung of Il1r1 −/− mice.…”
Section: Resultssupporting
confidence: 93%
“…Jia et al [ 25 ] showed in a mouse model of COPD that GPR183 is required for the formation of inducible bronchus-associated lymphoid tissue (iBALT), a secondary lymphoid-like structure within the lung. The iBALTs are also formed during Mtb infection and correlate with protection [ 33 ]. The initial host determinants that govern the induction of iBALT formation during Mtb infection remain to be elucidated, but it is possible that oxysterols and GPR183 play a major role in iBALT formation during TB by serving as recruitment and retention signals.…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al showed in a mouse model of COPD that GPR183 is required for the formation of inducible bronchus-associated lymphoid tissue (iBALT), a secondary lymphoid-like structure within the lung [25]. iBALTs are also formed during Mtb infection and correlate with protection [33]. The initial host determinants that govern the induction of iBALT formation during Mtb infection remain to be elucidated, but it is possible that oxysterols and GPR183 play a major role in iBALT formation during TB by serving as recruitment and retention signals.…”
Section: Discussionmentioning
confidence: 99%